Non-injection drug use among incarcerated people in Iran: Findings from three consecutive national bio-behavioral surveys - Mahkameh Rafiee; Mohammad Karamouzian; Mohammad Sharifi; Ali Mirzazadeh; Mehrdad Khezri; Ali Akbar Haghdoost; Soheil Mehmandoost; Hamid Sharifi (BMC, 2024)
Abstract Background Prisons often serve as high-risk environments for drug use, and incarcerated people are at a high risk for substance use-related mental and physical harms. This study aimed to determine the prevalence of non-injection drug use inside the prison and its related factors among incarcerated people in Iran. Methods We utilized data from three national bio-behavioral surveillance surveys conducted among incarcerated people in Iran in 2009, 2013, and 2017. Eligibility criteria were being ≥ 18 years old, providing informed consent, and being incarcerated for over a week. Overall, 17,228 participants across all surveys were recruited through a multi-stage random sampling approach. Each participant underwent a face-to-face interview and HIV test. The primary objective of the study was to assess self-reported non-injection drug use within the prison environment within the last month. A multivariable logistic regression model was built to determine associated covariates with drug use inside prison and an adjusted odds ratio (aOR) with 95% confidence intervals (CI) were reported. Result The prevalence of non-injection drug use inside the prison was 24.1% (95% CI 23.5, 24.7) with a significant decreasing trend (39.7% in 2009, 17.8% in 2013, 14.0% in 2017; p-value < 0.001). Overall, 44.0% of those who used drugs were also receiving opioid agonist therapy (OAT) and we noted that in 2017, 75.1% of those on OAT used stimulants. In the multivariable logistic regression model, the year of interview (2013: aOR = 1.43 and 2009: aOR = 5.60), younger age (19-29: aOR = 1.14 and 30-40: aOR = 1.37), male sex (aOR = 3.35), < high school education (aOR = 1.31), having a history of previous incarceration (aOR = 1.26), and having a history of lifetime HIV testing (aOR = 1.76) were significantly and positively associated with recent non-injection drug use inside the prison. Conclusions Approximately one in four incarcerated people in Iran reported drug use within the last month inside prisons. While a declining trend in non-injection drug use was noted, substantial gaps persist in harm reduction programs within Iranian prisons. In particular, there is a pressing need for improvements in drug treatment programs, focusing on the integration of initiatives specifically designed for people who use stimulants.